Implementing Quality Function Deployment (QFD) to enhance competitiveness and user satisfaction in industrial lubricants - Siskayanti, Rini; Iridiastadi, Hardianto (Sainteks: Jurnal Sain dan Teknik, 2025)
Along with the development and progression of sophisticated engine technology will have an impact on the high level of competition in the lubricant business. This will provide a great opportunity for consumers to find a quality lubricant products at competitive rates. The main objective of this research is to make improvements industrial lubricant that can be developed and improve product quality by analyzing the attributes attached based on customer wants and needs.One of the appropriate methods to solve that problems is Quality Function Deployment (QFD).The data obtained from surveys to customers later translated into the House of Quality (HOQ), then do the analysis. Based on the data analysis afterward be produced expansions proposals according to quality and priority attributes considered important by customers. There are 16 attributes considered important by customers who are grouped into 4 dimensions in the order of priority Place, Price, Product, and Promotion. Of performance industrial lubricant obtained that Product attribute is the most satisfying consumers when compared with competitors. The next sequence is Promotion, Place, and Price.The main priority should be improved for the development of industrial lubricant product is to increase knowledge of human resource and business partners, improvements to the lubricant delivery system by performing a model consignment and optimizing laboratory facilities that have been held so expect industry lubricant products manufactured by PT. XY and consumers demand a wider marketing.